(untitled) (Педагогіка вищої та середньої школи, 2009)
The Article is devoted to the study of the intellectual abilities and motivation of the achievement in the structure of the professional competence from the standpoint of foreign scientists. It concerns the particularities of the different rections of the intellectual abilities’ hierarchical structure, their functioning at different stages of human life as referred to the realization of the professional activity. The paper investigates motivational aspects in unity of the personality’s interests and motivation of the achievement. The structure of the desires and actions directed to the realization of the personality’s need for achievement is under the view.